2013
DOI: 10.1192/pb.bp.112.038703
|View full text |Cite
|
Sign up to set email alerts
|

Compulsion in the community: mental health professionals' views and experiences of CTOs

Abstract: Aims and methodWe surveyed the views and experiences of all mental health professionals in adult community mental health teams and approved mental health professionals in 2Gether and Oxford Health NHS Foundation Trusts, regarding the use of community treatment orders (CTOs).ResultsA total of 288 surveys were completed (response rate 48%). Forty-eight (83%) psychiatrists and 142 (67%) non-psychiatrist mental health professionals were in favour of CTOs. The decision-making regarding CTOs was overwhelmingly clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Different understandings of the patient’s healthcare needs can complicate the therapeutic alliance [ 10 ]. Our results showing that therapists justified OC as a means to support the patient concur with findings in other studies [ 11 , 14 , 27 ]. This also agrees with the fact that three out of four OC decisions in Norway are based on an assessment of the patient’s treatment needs [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Different understandings of the patient’s healthcare needs can complicate the therapeutic alliance [ 10 ]. Our results showing that therapists justified OC as a means to support the patient concur with findings in other studies [ 11 , 14 , 27 ]. This also agrees with the fact that three out of four OC decisions in Norway are based on an assessment of the patient’s treatment needs [ 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…The participants felt that the coercive framework of OC challenged their therapeutic relationship, the coercion itself becoming a burden. Other studies have demonstrated the same concerns [ 14 , 27 ]. It was difficult to assess when the benefits outweighed the drawbacks, especially where clinicians assessed the treatment effect of coercion as small.…”
Section: Discussionsupporting
confidence: 61%
“…There are some studies internationally on what professionals think of CCT, they find generally positive attitudes towards CCT [9][10][11][12][13]. We could not find any studies that identify mental health care workers' opinions on CTH.…”
Section: Introductionmentioning
confidence: 65%
“…Many patients subject to CTOs had a recent history of treatment discontinuation, and as other studies show, CTOs were described as a clinical tool to promote treatment adherence to stabilize the patients’ condition and to prevent hospital re-admission [ 14 , 15 , 20 23 ]. The participants emphasized the importance of communication and of facilitating patient cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Even if patients describe CTOs as less coercive than hospital admissions, many patients dislike having to take medications and experience that they have little influence on treatment decisions [ 16 19 ]. Studies show that health professionals value the CTO scheme for providing security and structure after discharge from hospital [ 14 , 15 , 20 23 ]. Health professionals often describe CTOs as a useful tool to facilitate stable medication and follow-up because of the patients’ lack of insight [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%